Modifikasi Serat Limbah Kubis Menjadi Nanokristalin Selulosa Melalui Metode Hidrolisis Asam: Waste Cabbage Fibers Modification Into Nano-Crystalline Cellulose Via Acid Hydrolysis Method - Arjuna, Andi; Natsir, Selva; Khumaerah, Andi Amelia; Yulianty, Risfah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
As one of vegetable plants in South Sulawesi, cabbage (Brassica oleracea L.) crops has generated cellulose fibers biomass which is potentially modified into nano-crystalline cellulose, a valuable material in the pharmaceutical formula. Therefore, this study aims to manipulate the natural cellulose fibers of cabbage biomass through acid hydrolysis method within product preliminary evaluation through FT-IR and XRD. The fibers were modified through the bleaching process produce micro crystalline cellulose, which was then hydrolyzed with 65% sulfuric acid to obtain nanocrystalline cellulose. The products have yellow pale to brown colour, with a yield of 10.06% and 31.16% respectively. Based on FT-IR spectra, both products inherit cellulose characteristics, C-O (1232.16 cm-1); C = O (1743.65 cm-1); -OH (1625.99 cm-1); C-H (2920.23 cm-1); O-H (3414 cm-1). The increasing trend of crystallinity index during the process was also observed in XRD diffractogram. It is identifiable from 7.41% for natural fiber, 69.68% for crystalline microcrystalline, and 78.01% for nano crystalline cellulose. Through MatchÂ®, the estimated crystalline product size reaches 58.91 nm.